2018
DOI: 10.1186/s12284-018-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Tibetan Plateau annual wild barley (Hordeum spontaneum) HsCIPKs enhances rice tolerance to heavy metal toxicities and other abiotic stresses

Abstract: BackgroundThe calcineurin B-like protein (CBL) and CBL-interacting protein kinase (CIPK) signaling system plays a key regulatory role in plant stress signaling. The roles of plant-specific CIPKs, essential for CBL-CIPK functions, in the response to various abiotic stresses have been extensively studied so far. However, until now, the possible roles of the CIPKs in the plant response to heavy metal toxicities are largely unknown.ResultsIn this study, we used bioinformatic and molecular strategies to isolate 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The same function is not found for the homologous gene AtCBL9 [126]. In annual wild barley (Hordeum spontaneum) grown on the Tibetan Plateau, multiple HsCIPKs (HsCIPK-2, -5, -17, -28, -29, and -30) are regulated by abiotic stresses, including multiple heavy metals, and overexpression of each HsCIPK in rice enhances root tolerance to heavy metal toxicity, salt stress, and drought stress [138]. The relationship among HsCIPKs in the regulation of heavy metal responses should be examined in depth.…”
Section: Functions Of the Cbl-cipk Pathwaymentioning
confidence: 90%
“…The same function is not found for the homologous gene AtCBL9 [126]. In annual wild barley (Hordeum spontaneum) grown on the Tibetan Plateau, multiple HsCIPKs (HsCIPK-2, -5, -17, -28, -29, and -30) are regulated by abiotic stresses, including multiple heavy metals, and overexpression of each HsCIPK in rice enhances root tolerance to heavy metal toxicity, salt stress, and drought stress [138]. The relationship among HsCIPKs in the regulation of heavy metal responses should be examined in depth.…”
Section: Functions Of the Cbl-cipk Pathwaymentioning
confidence: 90%
“…It is thus not surprising that overexpression of CaMs (Zhou S. et al, 2016), CBLs (Cheong et al, 2003; Cheong et al, 2010), CIPKs (Pan et al, 2018), or CDPKs (Xu et al, 2010; Asano et al, 2012), even exogenous supplement of CaCl 2 (Ahmad et al, 2018), all enabled plants to bear salt toxicity. Remarkably, transgenic rice harboring CIPKs from wild barley ( Hordeum spontaneum ) displayed enhanced tolerance to drought and heavy metals as well.…”
Section: Regulatory Network Underlying Defense Systemsmentioning
confidence: 99%
“…Remarkably, transgenic rice harboring CIPKs from wild barley ( Hordeum spontaneum ) displayed enhanced tolerance to drought and heavy metals as well. Besides, some HsCIPKs were also subject to induction by cold, heat and ABA (Pan et al, 2018). However, the behavior of Arabidopsis cbl1 mutant upon cold exposure was really inconsequent, with higher (Cheong et al, 2003), similar (Albrecht et al, 2003), and lower (Huang et al, 2011) tolerance all being reported.…”
Section: Regulatory Network Underlying Defense Systemsmentioning
confidence: 99%
“…The overexpression of ZmCIPK8 from Zea mays confers drought tolerance in transgenic tobacco [22], and overexpression of TaCIPK27 increases tolerance to drought, but decreases sensitivity to ABA treatment in transgenic Arabidopsis [23]. Overexpression of each of the 12 HsCIPKs from barley (Hordeum spontaneum) in rice shows that all but HsCIPK28 enhance the tolerance of roots to multiple heavy metal toxicities, and eight HsCIPKs (except for HsCIPK9, HsCIPK11, HsCIPK14, and HsCIPK24) improve the tolerance to salt, drought, and ABA [24]. Overexpressing the LlaCIPK gene from Lepidium can enhance cold tolerance in tobacco by increasing the level of proline and cell membrane stability [25].…”
Section: Introductionmentioning
confidence: 99%